Managing head injury risks in competitive skateboarding: what do we know? - McIntosh, A. S.; Patton, D. A.; McIntosh, A. G. D. (British Journal of Sports Medicine, 2021)
Objectives: The broad objective of this paper is to inform policy, practice and research regarding the management of head injury risks in competitive skateboarding. The main motivation for the current study was the question of mandating helmet use in competitive skateboarding. The specific aims are to present current knowledge on (A) head injury risks in skateboarding, (B) preliminary biomechanical data on falls and head injury risks in a selection of competitive skateboarding events similar to those planned for the Summer Olympics, (C) standards for skateboard-styled helmets and (D) impact performance of helmets commonly used in skateboarding. Methods: A narrative review of the published literature on head injuries in skateboarding was conducted. Videos of skateboarding competitions from Vans Park Professional League, Street League Skateboarding and Dew Tour were reviewed to describe crashes and falls. Standards databases including the International Organization for Standardization (ISO), British Standards Institution (BSI), Snell, United States Consumer Product Safety Commission (CPSC) and American Society for Testing and Materials (ASTM) were searched for skateboarding-styled helmet standards. A sample of helmets considered suitable for skateboarding was tested in standard impact tests.Results The majority of previous literature focused on the paediatric population in a recreational setting with little data from competitive skateboarding. Head injuries comprised up to 75% of all injuries and helmet use was less than 35%. Video analysis identified high rates of falls and crashes during competitive skateboarding, but also a capacity for the athletes to control falls and limit head impacts. Less than 5% of competitive skateboarders wore helmets. In addition to dedicated national skateboard helmet standards, there are several national standards for skateboard-styled helmets. All helmets, with the exception of one uncertified helmet, had similar impact attenuation performance; that is, at 0.8 m drop height, 114-148 g; at 1.5 m, 173-220 g; and at 2.0 m, 219-259 g. Impact performance in the second impact was degraded in all helmets tested.